(untitled) (Revista horizonte, 2011)
This article measures the effects of an endurance exercise program on plasma, anthropometric and cardiovascular variables related to the health of obese women. The methodology is applied in 34 obese women who were assigned to an aerobic training group (n=17), which trained for 13 weeks; the remaining 17 women participated as a control group (n=17). Total cholesterol (TC), LDL cholesterol (LDL), HDL cholesterol (HDL), plasma triglycerides (TGP), fasting glucose (Gl), total body weight (BW), body mass index (BMI), waist circumference (WC), fat mass (FM), muscle mass (MM), systolic blood pressure (SBP), diastolic blood pressure (DBP) and resting heart rate (HRF) were measured before and after the 13 weeks of training. The main result is that the training favorably modified the lipid, anthropometric and cardiovascular profile of the women.